Review of Criteria for Commendable Behavior and Expectations for Improvement During the Probationary Period - Sayadi, Ahmad (UNES Law Review, 2024)
Indonesia is one of the countries that still maintains death penalty, as stipulated in article 10 of the old Criminal Code. Death penalty is one of the main punishments as well as the heaviest punishment for criminal offenders. Meanwhile, based on its renewal based on Law No.1 of 2023 concerning the new Criminal Code. Death penalty is no longer included in the category of main punishment, but a special punishment that is always threatened alternatively and imposed with a probation period of 10 (ten) years. Article 100 of the new Criminal Code is one of the articles born from the reformation of the new Criminal Code which has become pros and cons in the community. The reason is that this provision states that the judge can impose death penalty with a probation period of 10 (ten) years by taking into account the provisions of commendable behavior and hope for improvement. If during the probation period the convict shows commendable behavior, then the death penalty can be changed into life imprisonment. On the other hand, if during the probation period the convict does not show commendable behavior and hope for reparation, then death penalty can be imposed by order of the attorney general based on presidential decree by considering the decision of the Supreme Court. Thus, the question arises as to what the criteria for commendable behavior and hope for improvement are. As a basis for the judge's consideration in deciding whether or not the convict deserves a change in sentence.